2016
DOI: 10.1111/j.1728-4465.2016.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Adolescent Girls in Socially Conservative Settings: Impacts and Lessons Learned from the Ishraq Program in Rural Upper Egypt

Abstract: In rural Upper Egypt, adolescence is a critical period in girls' transition to adulthood during which they are at risk for a number of negative outcomes, including restricted mobility and early marriage and childbearing. This study evaluates and presents lessons learned from Ishraq, an educational program that established safe spaces for out-of-school adolescent girls in rural Upper Egypt. Baseline and endline surveys were administered to all households containing an eligible girl in the program areas. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…27 An evaluation of the scale-up of Ishraq reported that girls' reading comprehension and multiplication skills improved (Table 2). 23…”
Section: Education-related Outcomesmentioning
confidence: 99%
“…27 An evaluation of the scale-up of Ishraq reported that girls' reading comprehension and multiplication skills improved (Table 2). 23…”
Section: Education-related Outcomesmentioning
confidence: 99%
“…These authors indicate that affirmative action may have disruptive effects (Deininger et al, 2015), may backlash against women (Gagliarducci and Paserman, 2011), or may just not eliminate negative stereotypes (Coate and Loury, 1993). studies have focused on the impact of educational programs on women in conservative regions (Sieverding and Elbadawy, 2016;Elsayed and Roushdy, 2017). Sadania (2016) connectswomen's labor market participation and their say within Egyptian households, showing that the empowering effect of employment depends on the type of occupation.…”
Section: Literature and Contributionmentioning
confidence: 99%
“…studies have focused on the impact of educational programs on women in conservative regions (Sieverding and Elbadawy, 2016;Elsayed and Roushdy, 2017). Sadania (2016) connects women's labor market participation and their say within Egyptian households, showing that the empowering effect of employment depends on the type of occupation.…”
Section: Literature and Contributionmentioning
confidence: 99%